2017
DOI: 10.18632/oncotarget.15553
|View full text |Cite
|
Sign up to set email alerts
|

The angiotensin receptor blocker, Losartan, inhibits mammary tumor development and progression to invasive carcinoma

Abstract: Drugs that target the Renin-Angiotensin System (RAS) have recently come into focus for their potential utility as cancer treatments. The use of Angiotensin Receptor Blockers (ARBs) and Angiotensin-Converting Enzyme (ACE) Inhibitors (ACEIs) to manage hypertension in cancer patients is correlated with improved survival outcomes for renal, prostate, breast and small cell lung cancer. Previous studies demonstrate that the Angiotensin Receptor Type I (AT1R) is linked to breast cancer pathogenesis, with unbiased ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 50 publications
(66 reference statements)
2
66
0
Order By: Relevance
“…Immunohistochemistry was performed using antibodies directed against pSTAT3, Ki67, and b-catenin as previously published (Putoczki et al, 2013;Phesse et al, 2014;Coulson et al, 2017). 4lm-thick sections from paraffin blocks were re-hydrated, antigen retrieval performed with citrate buffer (0.1%) by microwaving for 15 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Immunohistochemistry was performed using antibodies directed against pSTAT3, Ki67, and b-catenin as previously published (Putoczki et al, 2013;Phesse et al, 2014;Coulson et al, 2017). 4lm-thick sections from paraffin blocks were re-hydrated, antigen retrieval performed with citrate buffer (0.1%) by microwaving for 15 min.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The clear in-vivo effects of AT1R blockers shown in animal cancers by various authors, and now amply confirmed by Coulson et al [1], have all been obtained using very high doses. In their paper, mice received 70mg losartan/kg/day, compared with the normal range of 20-100mg per day for adult patients.…”
mentioning
confidence: 70%
“…The paper by Coulson et al [1] provides some of the most comprehensive evidence to date that an angiotensin type 1 receptor blocker, losartan, has highly beneficial effects on mammary tumor development and progression to invasive carcinoma in experimental animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RAS also plays a role in cancer, for example, Ang II has been shown to promote adhesion, proliferation, migration and angiogenesis resulting in the development of an array of varying cancers . Several studies have linked the presence and more specifically the upregulation of AGTR1 (the gene that codes the AT1 R) to the pathogenesis of certain cancers, particularly invasive breast carcinoma . Studies have also linked ACE2 expression and its potential mechanism in numerous cancer cells and tissues by counter regulating ACE activity .…”
Section: Role Of Ras In Cancer Cellsmentioning
confidence: 99%